Вивчення термічних і трибологічних властивостей ароматичних поліамідів - Чигвінцева, Ольга Павлівна; Chigvintseva, Olga; Рула, Ірина Василівна; Rula, Irina; Бойко, Юлія Володимирівна; Boiko, Yuliya (Луцький національний технічний університет, 2019)
Проведені порівняльні термічні і трибологічні дослідження ароматичних поліамідів фенілон С-1 і фенілон П. Вивчені процеси термоокиснювальної деструкції поліамідних в’яжучих. Досліджений вплив режимів експлуатації на процеси тертя та зносу полімерів. Показано, що ароматичні поліаміди при роботі у режимі тертя без змащування мають низький коефіцієнт тертя і високу зносостійкість.Comparative thermal and tribological studies of aromatic polyamides phenylone C-1 and phenylone P have been carried out. Thermo-oxidative destruction processes of polyamide binders have been studied. It is established that phenylone C-1, has a higher heat resistance and begins to decompose at a temperature of 55°C higher than phenylone P. The influence of operating modes on the processes of friction and wear of polymers is investigated. It was found that phenylone P is a more promising material according to tribotechnical characteristics. This polymer has a low coefficient of friction and minimal wear. It has been shown that aromatic polyamides have high tribotechnical characteristics when operating under friction conditions without lubrication and can work stably in friction units with the performance criterion PV 0.7 MPa m/s.
Study of thermal and tribological properties of aromatic polyamides
Keywords: ароматичний поліамід фенілон; аromatic polyamide phenylene; термостійкість; thermal stability; коефіціент тертя; coefficient of friction; інтенсивність лінійного зношування; intensity of linear wear